Bioethanol production from Madhuca latifolia L. flowers by a newly isolated strain of Pichia kudriavzevii. Issue 8 (December 2019) - Agrawal, Tripti; Quraishi, Afaque; Jadhav, Shailesh Kumar
There is a growing interest worldwide to search new, cheap and non-food biomass source for ethanol production. Bioethanol is a liquid fuel produced from renewable biomass source. In the present study, ethanol production from flowers of Madhuca latifolia trees was investigated by yeast strain isolated from milk whey. The isolated yeast was screened for fermentation ability by carbohydrate fermentation test and subjected to fermentation using M. latifolia flowers as substrate. The isolated yeast strain was identified as Pichia kudriavzevii on the basis of sequencing of D1/D2 domain of rRNA gene through basic local alignment search tool and molecular phylogenetic analysis. Maximum ethanol production, 371 g kg −1 from the flowers was achieved via optimizing operational parameters; a fermentation duration of 48 h, temperature 25°C, and pH 5.0. The effect of nitrogen supplements, enzymatic treatment and co-culture on bioethanol production with the optimized conditions revealed that the optimal condition could produce maximum ethanol without any supplementation or treatment. Co-culturing of P. kudriavzevii strain with Pichia stipitis NCIM 3497 was able to enhance ethanol production. The present study provides baseline information for further scale up of bioethanol production process on industrial level using M. latifolia flowers as a cheap and non-food biomass source.